THE IMPLEMENTATION STRATEGY OF QMS INFORMATION TECHNOLOGY PROJECT: CHALLENGES & BENEFITS - Deitje S. Pongoh; Sonny R. Kasenda; Veny V. Ponggawa; Billy Liunsanda; Putri Angellita (Interdisciplinary Journal of Advanced Research and Innovation, 2023)
It cannot be denied that many types of information projects have emerged. However, because of this convenience, many people forget that the quality of a project is also essential in supporting it to last long and getting good feedback from users of the products or services produced by a project. This journal uses a qualitative research method, where existing research results will be reviewed to get a new view. There are several objectives of this study: 1) Knowing the Strategy for Implementing the Quality Management System in Informatics projects, 2) why a Quality Management System is needed in Informatics projects, 3) implementing the Quality Management System in Informatics projects, what are the challenges, 4) Behind a challenge or risk, there is an advantage. There are benefits of applying the Quality Management System to the Informatics project. The research instruments used are observational and interview guidelines. The result is to find out the strategies that can be made to implement the Quality Management System so that this project can improve its quality and can also have an impact in the future on other Informatics projects.